Moringa oleifera and cratylia argentea: potential fodder species for ruminants in Nicaragua - Reyes Sanchez, N. (Uppsala (Suecia), 2006)
Sumario (En)
Ilus.; 286 ref.
Tesis (Dr)
Keywords: MORINGA OLEIFERA; CRATYLIA; VACAS LECHERAS; BIOMASA; VALOR NUTRITIVO; DIGESTIBILIDAD; ESPACIAMIENTO; ORDEÑO; NICARAGUA; PRODUCCION DE BIOMASA